2021
DOI: 10.1038/s41589-021-00776-9
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide screens uncover KDM2B as a modifier of protein binding to heparan sulfate

Abstract: Heparan sulfate (HS) proteoglycans bind extracellular proteins that participate in cell signaling, attachment, and endocytosis. These interactions depend on the arrangement of sulfated sugars in the HS chains generated by well-characterized biosynthetic enzymes; however the regulation of these enzymes is largely unknown. We conducted genome-wide CRISPR/Cas9 screens with a small molecule ligand that binds to HS. Screening of A375 melanoma cells uncovered additional genes and pathways impacting heparan sulfate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…PAPSS1 and PAPSS2 , CANT1 , and IMPAD1/BPNT2 encoding PAPS synthases 1 and 2, calcium-activated nucleotidase 1/UDP-diphosphatase, and 3′-phosphoadenosine 5′-phosphate 3′-phosphatase, respectively, were also listed. Furthermore, genes encoding regulators of GAG biosynthesis such as maintenance of Golgi-resident glycosyltransferases ( GOLPH3 ) ( Chang et al, 2013 ), a Golgi-localized protease ( SPPL3 ) ( Kuhn et al, 2015 ), a transcriptional regulator ( ZNF263 ) ( Weiss et al, 2020 ), and an epigenetic factor ( KDM2B ) ( Weiss et al, 2021 ) were also added to the list. In total, 66 genes were listed in these categories ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAPSS1 and PAPSS2 , CANT1 , and IMPAD1/BPNT2 encoding PAPS synthases 1 and 2, calcium-activated nucleotidase 1/UDP-diphosphatase, and 3′-phosphoadenosine 5′-phosphate 3′-phosphatase, respectively, were also listed. Furthermore, genes encoding regulators of GAG biosynthesis such as maintenance of Golgi-resident glycosyltransferases ( GOLPH3 ) ( Chang et al, 2013 ), a Golgi-localized protease ( SPPL3 ) ( Kuhn et al, 2015 ), a transcriptional regulator ( ZNF263 ) ( Weiss et al, 2020 ), and an epigenetic factor ( KDM2B ) ( Weiss et al, 2021 ) were also added to the list. In total, 66 genes were listed in these categories ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings on the IHC (Figure 5 ) indicate that the anti‐dsGAG/NA clones would exhibit broad antitumor effects. It is well known that HS/heparin captures heparin‐binding growth factors 20 , 44 ; therefore, we sought to determine whether the anti‐dsGAG/NA clones inhibit these tumor‐promoting functions of the dsGAG. However, neither neutralizing effects for heparin‐binding growth factors (FGF7 and HB‐EGF) nor inhibitions of cell invasion were observed (Figure S6A–E ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently reported the development of a genome-wide CRISPR screen to uncover novel factors regulating HS assembly in human cells. This genetic screen uncovered many potential regulatory pathways for HS biosynthesis and, importantly, revealed that the histone demethylase, KDM2B, controls HS-protein interactions via epigenetic regulation of SULF1 expression ( 128 ). Another CRISPR screen designed to identify host factors of Sindbis virus infection found that mutating COG4 , a member of the conserved Golgi complex, results in a defect in HS biosynthesis in human colorectal carcinoma cells ( 129 ).…”
Section: Regulatory Mechanisms Of Glycosaminoglycan Assemblymentioning
confidence: 99%